Analysis of Business Strategy and Growth of Sari Roti in the Indonesian Market - Dewi Puspaningtyas Faeni; Bahagia Juwanda Surbakti (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
This study analyzes the business strategy and growth of PT Nippon Indosari Corpindo Tbk, widely recognized by its brand name Sari Roti, within the Indonesian market. Established in 1995, Sari Roti has grown to become a dominant player in the modern bread industry in Indonesia. By employing a qualitative approach with a detailed case study, this research explores the various facets of the company's